2019
DOI: 10.1055/a-1017-3048
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum C-Peptide Level and Cardiovascular Autonomic Neuropathy According to Estimated Glomerular Filtration Rate in Individuals with Type 2 Diabetes

Abstract: Objective To investigate the association between serum C-peptide level and cardiovascular autonomic neuropathy (CAN) in individuals with type 2 diabetes mellitus (DM) according to estimated glomerular filtration rate (eGFR) Methods In a cross-sectional study, we examined 939 individuals with type 2 DM. We measured fasting C-peptide, 2-hour postprandial C-peptide, and ΔC-peptide (postprandial C-peptide minus fasting C-peptide) levels. The individuals were classified into 2 groups based on eGFR: individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The effect of C-peptide in type 2 diabetic patients is controversial and more complicated. Serum C-peptide levels were reported to be inversely associated with the prevalence of diabetic retinopathy and cardiovascular autonomic neuropathy in patients with T2DM [ 29 , 30 ]. Low C-peptide level was associated with increased cardiovascular risk in T2DM [ 31 ], even if glucose variation or severe hypoglycemia was considered [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of C-peptide in type 2 diabetic patients is controversial and more complicated. Serum C-peptide levels were reported to be inversely associated with the prevalence of diabetic retinopathy and cardiovascular autonomic neuropathy in patients with T2DM [ 29 , 30 ]. Low C-peptide level was associated with increased cardiovascular risk in T2DM [ 31 ], even if glucose variation or severe hypoglycemia was considered [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a higher level of fasting C-peptide was negatively associated with DPN, which was consistent with a previous study indicating that the C-peptide level was negatively associated with cardiovascular autonomic neuropathy in individuals with T2DM. 48 But a study in Denmark revealed that C-peptide ≥1550 pmol/L was associated with DPN. 49 It was also reported that C-peptide improved neuropathy in type 1 diabetic BB/Wor-rats.…”
Section: Author Contributionsmentioning
confidence: 99%
“…The data storage system on which it was established integrated obese and lean individuals with normalized T2D and glycemic metabolism, but not pregnant women, infants, obese subjects type-1 diabetes mellitus, but the approach has been utilized in these groups. Moreover, in [11], the dependency of C-peptide rate constants, particularly C-peptide evacuation, on subject characteristics is embedded in thresholds (on BMI and glycemic metabolism) rather than being continuous. When the boundaries are crossed, this might cause false variations in C-peptide clearance, which could be problematic in longterm investigations.…”
Section: Assessment Of Thyroxine Secretionmentioning
confidence: 99%